Γb- regular, γb- normal, and γb- connected spaces. Issue 5 (4th July 2021) - Hussein, Hanan Ali
Abstract: The concepts of γ b - regular space, γ b - normal space, and γ b - connected spaces are introduce. It is shown that every γ b - normal and b - γ - T 1 - space is γ b - regular.